Citizen's social responsibility towards health institutions - فرج, م. جرو محمد فرج; ا.م, د. كردستان عمر محمد محمد (Sulaimani Journal for Humanities, 2025)
This research aims to present a scientific interpretation of the principles, dimensions, types, and methods of assuming social responsibility toward health institutions. Draw from the literature and previously conducted scientific research related to the role of social responsibility in public health, based on the scientific basis of motivational theory and specifically rational choice theory. Needs are the basic motivation for citizens to take social responsibility towards health institution, It is a meaningful, rational, conscious, intelligent, diligent, purposeful, and active behavior, It is the result of social development and is linked to social intelligence through socialization and social education, It develops gradually with age, becomes stable in maturity, and appears suddenly and dynamically in specific situations, as a moral principle and a living social organizer that is the first duty of the ego in personality and the basis for self-respect and the type of treatment and relationships between infant and his/her mother, which watches over him/her and provide needs for him/her, and gradually shaped and established in the stages of maturity with full perfection of mind and consciousness which is completely shaped and stabilized in adult. The social responsibility of the citizen towards the health institution is related to the positive commitment between them and is two-part and one-way, Part of it depends on the motivation of the citizen's needs, the other part depends on the health institution according to its position and role in society. The two parts of the citizen's social responsibility to the health institution are one-way. The point of the citizen's social responsibility to the health institution is different from the point of the health institution's social responsibility, because the motivation to take social responsibility between individuals and health institutions are the same but at different points, they both complement each other, it depends on their self-direction and social orientation.
Keywords: social responsibility; public health; theoretical foundation of social responsibility; dimension of social responsibility; type of social responsibility; and method of social responsibility